PENGARUH PEMBELAJARAN AKIDAH AKHLAK TERHADAP PERILAKU SISWA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Syaharani, Lulu; Humaeroh , Iis; Utami, Dewi (Sindoro: Cendikia Pendidikan, 2024)
Madrasah Ibtidaiyah Ma'had Al-Zaytun is one of the madrasa-based educational institutions that has a commitment to form students to be berakhlaqul karimah in accordance with a solid and strong foundation of faith. The purpose of this research is to see the effect of learning akidah akhlak on the behavior of fifth grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. This research uses mixed methods or often referred to as mixed methods. In relation to this study, researchers used mixed methods research with a embedded design. The data collection methods used were questionnaires, observations, and interviews. The results of this study show that the learning process of moral creed for grade V students applies a variety of learning methods, including lectures plus, group assignments, literacy, discussions, and educational games. Habituation and application of moral creed values are carried out through routine school activities such as morning roll call, environmental picket, praying on time, and implementing 5S and 3 Advanced Cultures. This is also in line with the role of teachers in integrating Akidah Akhlak values into students' daily lives and providing good examples in carrying out religious teachings and moral values. The results of quantitative analysis showed a t test of 3.361> 2.026. To find out the category of the level of influence of research between variables, an analysis was carried out using an r value of 0.494 = 49.40% which is between the values of 0.400 - 0.599 in the high enough category. So based on these results it explains that the Ha hypothesis is accepted and the Ho hypothesis is rejected. Keywords: Akidah Akhlak Learning, Student Behavior